IMPLIKASI PENGGUNAAN GADGET PADA PERILAKU SOSIAL REMAJA - Sarifuddin, Nurul Ain Binti; Pribadi, Imam; Marhani (IKIP Siliwangi, 2026)
This study aims to describe the implications of gadget use on the social behavior of adolescents in Bone Tua Village, Masamba District, North Luwu Regency. This research uses a qualitative method with a phenomenological approach. The research informants consisted of 5 people with adolescent criteria who used gadgets and indications of social behavior, so that the technique used in determining informants was the purposive sampling technique. Data was collected through interviews, observations, and documentation, then analyzed by data reduction steps, data presentation, and conclusion drawn. The validity of the data is strengthened through source triangulation, triangulation techniques, and member checking. The results of the study show that the use of gadgets has two sides of influence. On the one hand, gadgets facilitate communication, provide access to knowledge, and encourage creativity and digital skills of teenagers. On the other hand, uncontrolled use of gadgets has a negative impact on reduced face-to-face interaction, weakened empathy, the emergence of individualistic behavior, a tendency for social isolation, and dependence on cyberspace, Thus, based on the results of data analysis obtained through interviews, observations, and documentation, it can be concluded that the use of gadgets has a significant influence on the formation of adolescent social behavior. The findings of the study show that gadgets have a positive impact, such as ease of communication and obtaining information, but also have a negative impact in the form of reduced direct social interaction, decreased empathy, and a tendency to social isolation if their use is not controlled. Therefore, the role of parents, teachers, and the social environment is indispensable in providing supervision, mentoring, and education so that the use of gadgets can be directed wisely, balanced, and still beneficial for the social development of adolescents.